2007
DOI: 10.1097/ta.0b013e3180487d0f
|View full text |Cite
|
Sign up to set email alerts
|

Range-of-Motion Restriction and Craniofacial Tissue-Interface Pressure From Four Cervical Collars

Abstract: Miami J and Philadelphia collars restricted CROM to the greatest extent. Miami J and Miami J/Occian back had the lowest levels of mandibular and occipital pressure; these collars may markedly reduce the risk of occipital pressure ulcers without compromising immobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…In those individuals, the collar or Vista Ò TS would serve as effective alternatives. Skin breakdown and pressure ulcers [32,33] due to prolonged usage have been documented in some patients particularly at the main contact points at the mandible, occiput, ears, shoulders, and clavicles. Prior studies have demonstrated that these complications may be reduced or eliminated with appropriate choice of newer, improved orthotics, an appropriate skin care regimen and monitoring, and proper fitting and application of the orthoses [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In those individuals, the collar or Vista Ò TS would serve as effective alternatives. Skin breakdown and pressure ulcers [32,33] due to prolonged usage have been documented in some patients particularly at the main contact points at the mandible, occiput, ears, shoulders, and clavicles. Prior studies have demonstrated that these complications may be reduced or eliminated with appropriate choice of newer, improved orthotics, an appropriate skin care regimen and monitoring, and proper fitting and application of the orthoses [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…When the train-of-four response was zero at the ulnar nerve, the neck was immobilised with an appropriately sized semirigid Philadelphia Patriot Ò cervical collar (Philadelphia Cervical Collar Co., Thorofare, NJ, USA), according to the manufacturer's instructions [18]. The head was taped to the trolley ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For the same outcome, we also identified very-low-quality evidence (downgraded for indirectness) from 13 nonrandomized studies [140][141][142][143][144][145][146][147][148][149][150][151][152] Seven additional studies [153][154][155][156][157][158][159] were not included in the final analysis because they were missing data (mean and/or SD of intervention and control group not reported).…”
Section: (Semi)rigid Collar (I) Compared With No Collar (C)mentioning
confidence: 99%